Adult Learning in the Context of the Interreligious Dialogue Process: A Collaborative Research Study Involving Christians, Jews and Muslims - Nadira K. Charaniya; Jane West Walsh (Adult Education Research Conference, 2001)
This paper reports on a collaborative qualitative research study where the purpose was to explore the nature of the learning that occurs in the interreligious dialogue process. Participants were 20 Christian, Jewish and Muslim adults who have participated in interreligious dialogue, for a period of more than a year.